Semantic Mapping as a Pre-Writing Strategy in the EFL Classroom: Voices from Teachers and Students - Pakaja, Marina; Habibie, Alvons; Akhmad, Enni; Nabu, Andiani Rezkita; Karmila, Karmila (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2025)
Semantic mapping is a widely recognized strategy in English language learning, particularly in the development of writing skills. Despite its proven effectiveness, limited attention has been given to its use at the pre-writing stage, especially in paragraph writing. This study aims to explore the perspectives of both teachers and students on the application of semantic mapping during the pre-writing phase and to identify the benefits and challenges associated with its implementation. A descriptive qualitative method was employed, involving two teachers and seventeen students from Muhammadiyah Junior High School in Gorontalo City. The findings revealed that both teachers and students held positive views about using semantic mapping before writing. They reported various benefits, although they also faced several challenges, particularly related to time constraints and students’ preparedness. The results of this study suggest that semantic mapping remains a valuable instructional tool that can be further developed and effectively integrated with emerging educational technologies.